Difficulties translating antisense-mediated activation of Frataxin expression from cell culture to mice. Issue 1 (31st December 2022) - Kilikevicius, Audrius; Wang, Jun; Shen, Xiulong; Rigo, Frank; Prakash, Thahza P.; Napierala, Marek; Corey, David R.
ABSTRACT: Friedreich's ataxia (FA) is an inherited neurodegenerative disorder caused by decreased expression of frataxin (FXN) protein. Previous studies have shown that antisense oligonucleotides (ASOs) and single-stranded silencing RNAs can be used to increase expression of frataxin in cultured patient-derived cells. In this study, we investigate the potential for oligonucleotides to increase frataxin expression in a mouse model for FA. After confirming successful in vivo delivery of oligonucleotides using a benchmark gapmer targeting the nuclear noncoding RNA Malat1, we tested anti- FXN oligonucleotides designed to function by various mechanisms. None of these strategies yielded enhanced expression of FXN in the model mice. Our inability to translate activation of FXN expression from cell culture to mice may be due to inadequate potency of our compounds or differences in the molecular mechanisms governing FXN gene repression and activation in FA model mice.